Synthesis, characterization and computational studies of Zn complex based on the 8-hydroxyquinoline group containing benzimidazole. Issue 54 (2nd September 2020) - Li, Shanji; Wen, Huawen; Yuan, Ningning; Xie, Pengbo; Qin, Jinlan; Wang, Zhengfang
Abstract : A novel fluorescent zinc complex with 8-hydroxyquinoline containing benzimidazole ligands has been designed and synthesized. And the ligand structural distortion could cause the blue shift in the emission profile of the complex. Abstract : A novel fluorescent zinc complex with 8-hydroxyquinoline containing benzimidazole ligands has been designed and synthesized. Its emission, IR spectroscopy, thermo-gravimetric analysis as well as electrochemical properties have been studied. The solid-state structures were determined via single crystal X-ray diffraction and powder X-ray diffraction. It was found that the ligands around the Zn atoms are distorted by the constrained coordination environment. Computational studies have also been performed to provide insights into the electronic transitions, excited state origins and electrochemical properties of the complex. Based on the observed luminescence phenomena and the quantum chemical calculated results, it was also investigated that the energy transfer mechanism for the luminescence of the complex, which indicated that the ligand structural distortion could cause the blue shift in the emission profile of the complex.